Investigación académica y de los recursos humanos en Salud - Miraval Rojas, Edgar Jesús (2012)
Considering that scientific evidence in our country is a topic to be addressed by state entities and private institutions; and taking into account that this area has been incorporated in the study programs in undergraduate courses in research methodology, and also having been reinforced in postgraduate courses in universities, we have a gap and a pending agenda for incorporating scientific evidence into our daily teaching and research activities. There are very few studies on scientific production in our country, very scarce indexed magazines and the local scientific production does not satisfy our expectations. Another factor is lack of financial support and motivation for doing research activities, and this makes things more difficult. Plenty of effort has to be undertaken in order to put together research connections between academic centers and healthcare institutions. Also, there is a great need for specialized training for doing research and create our own scientific evidence.